Preparation and characterisation of inexpensive porous kaolin hollow fibre as ceramic membrane supports for gas separation application - Abdulhameed, Mohammed Abdulmunem; Dzarfan Othman, Mohd Hafiz; Ismail, Ahmad Fauzi; Matsuura, Takeshi; A Rahman, Mukhlis; Harun, Zawati; Puteh, Mohd Hafiz; Jaafar, Juhana (Springer Nature, 2017)
Low-cost, porous ceramic kaolin-based hollow fibre membrane support (HFMS) for gas separation application was developed via phase inversion technique. The ceramic suspensions with various ratios of kaolin to polyethersulfone (PESf) binder (5:1 to 9:1) were extruded and then sintered at 1200 to 1500 °C. The HFMSs were characterised by several analyses to investigate the effects of kaolin/PESf ratio and sintering temperature on the sample properties. The results showed that the kaolin/PES ratio and sintering temperature affected the considerable structure and physical properties of the kaolin membrane. It is observed that with increasing sintering temperature, the porosity and gas permeation of the HFMS decreased, while the bending strength and density of the HFMS increased. As a result, a porous HFMS with sufficient mechanical strength and high gas permeation characteristics is achievable if the appropriate kaolin/PESf ratio and sintering temperature are chosen.